Elucidating dislocation core structures in titanium nitride through high-resolution imaging and atomistic simulations. (December 2022) - Salamania, J.; Sangiovanni, D.G.; Kraych, A.; Calamba Kwick, K.M.; Schramm, I.C.; Johnson, L.J.S.; Boyd, R.; Bakhit, B.; Hsu, T.W.; Mrovec, M.; Rogström, L.; Tasnádi, F.; et al.
Graphical abstract: Highlights: High-resolution scanning transmission electron microscopy was used to image dislocation core structures in TiN. Classical interatomic potential simulations complement the high-resolution images by confirming the atomic structure of the different dislocation types. Density-functional theory bonding analyses suggest enhanced metal–metal bonding at the cores compared to defect-free regions, locally weakening the directional Ti-N bonds. Complementary Peierls stress calculations predict substantial N vacancy-pinning effects at the dislocation core. Abstract: Although titanium nitride (TiN) is among the most extensively studied and thoroughly characterized thin-film ceramic materials, detailed knowledge of relevant dislocation core structures is lacking. By high-resolution scanning transmission electron microscopy (STEM) of epitaxial single crystal (001)-oriented TiN films, we identify different dislocation types and their core structures. These include, besides the expected primary a/2110 〈 1 1 – 0 〉 dislocation, Shockley partial dislocations a/6111 〈 11 2 – 〉 and sessile Lomer edge dislocations a/2100〈011〉. Density-functional theory and classical interatomic potential simulations complement STEM observations by recovering the atomic structure of the different dislocation types, estimating Peierls stresses, and providing insights on the chemical bonding nature at the core. The generated models of the dislocation cores suggest locally enhanced metal–metal bonding, weakened Ti-N bonds, and N vacancy-pinning that effectively reduces the mobilities of 110 〈 1 1 – 0 〉 and 111 〈 11 2 – 〉 dislocations. Our findings underscore that the presence of different dislocation types and their effects on chemical bonding should be considered in the design and interpretations of nanoscale and macroscopic properties of TiN.